COVID 19-Induced Smell and Taste Impairments: Putative Impact on Physiology - Meunier, Nicolas; Briand, Loïc; Jacquin-Piques, Agnès; Brondel, Laurent; Pénicaud, Luc (Frontiers in Physiology, 2021)
Smell and taste impairments are recognized as common symptom in COVID 19 patients even in an asymptomatic phase. Indeed, according to the country, up to 85 to 90 % of cases anosmia and dysgeusia are reported. We will review briefly the main mechanisms involved in the physiology of taste and olfaction focusing on receptors and transduction as well as the main neuroanatomical pathways. Then we will examine the current evidences, even if still fragmented and unsystematic, explaining the disturbances and mode of action of the virus at the level of the nasal and oral cavities. We will focus on its impact on peripheral and central nervous system. Finally knowing the role of smell and taste in numerous physiological functions, especially in ingestive behavior, we will consider the consequences on the physiology of the patients as well as its management.